2018
DOI: 10.21577/0100-4042.20170212
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Adsorção E Estudo Eletroquímico De Células Solares Produzidas Com Tio2 E Corante Extraído Do Hibiscus

Abstract: HIBISCUS. Dye-sensitized solar cells using natural dyes have lower cost when compared to rutheniumbased dyes. This paper aims to evaluate, electrochemically, solar cells composed of TiO 2 with dye extracted from the Hibiscus (var. Sabdariffa) and propose an adsorption model capable of predicting the adsorption mechanism of the dye on the semiconductor surface. The characterization techniques used were: Fourier Transform Infrared Spectroscopy, UV-VIS Spectroscopy, Measurement of the Open Circuit Potential, Phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The DRX confirm the production of niobium pentoxide by Pechini method with high crystallinity and free of impurities and the orthorhombic crystalline structure to Nb 2 O 5 , according to PDF 96-210-6535 of ICDD 16,17,18 . In general, the crystallization conditions of each Nb 2 O 5 structure Through analysis of FTIR shown in Figure 2, a band is observed in the region of 832-997 cm -1 that is attributed stretching of the Zn-O band was observed that when Nb 2 O 5 is added that band is shifted and intensified.…”
Section: Characterization Of Niobium Pentoxidementioning
confidence: 63%
See 3 more Smart Citations
“…The DRX confirm the production of niobium pentoxide by Pechini method with high crystallinity and free of impurities and the orthorhombic crystalline structure to Nb 2 O 5 , according to PDF 96-210-6535 of ICDD 16,17,18 . In general, the crystallization conditions of each Nb 2 O 5 structure Through analysis of FTIR shown in Figure 2, a band is observed in the region of 832-997 cm -1 that is attributed stretching of the Zn-O band was observed that when Nb 2 O 5 is added that band is shifted and intensified.…”
Section: Characterization Of Niobium Pentoxidementioning
confidence: 63%
“…A similar behavior for both diagrams is observed since bands respectively appearing in the 677-906 cm -1 region can be attributed to stretching of Zn-O and Nb-O bonds. Already a band in 1629-1230 and 1378-1507 cm -1 for a mixture of oxide and only ZnO can be attributed assigned to the asymmetric stretching modes of oxygens present in sample 18,19,20,21 . Figure 3 shows the X-ray fluorescence (XRF) spectrum.…”
Section: Characterization Of Niobium Pentoxidementioning
confidence: 99%
See 2 more Smart Citations
“…Este resultado de eficiência obtida comprova que para o TiO2, o corante da ameixa atingiu uma série de exigências, como gap adequado, 23 boa ancoragem do corante na superfície do óxido, 8 longo tempo de vida do estado excitado, 23 entre outros fatores, 8 quando comparado aos demais corantes testados, indicando também uma maior concentração de antocianidinas na composição do corante extraído da ameixa. 33 Em geral, células solares produzidas com corantes naturais apresentam eficiência próxima a valores de 0,05%, 34 0,15% 11 e 0,37% 34 raramente chegando a valores maiores que 1%. 11 O método extrativo utilizado e a selagem do dispositivo para as análises fotoeletroquímicas estão relacionados com os parâmetros aqui encontrados, porém não foram avaliados.…”
Section: Fotocronoamperometria (Fca)unclassified